5 cm OH Masers in Northern Star Formation Regions - Hai-Hua Qiao; Xu-Jia Ouyang; Zhi-Qiang Shen; Shari L. Breen; Kai Yang; Xi Chen; Juan Li (The Astronomical Journal)
We present a 6.0 GHz excited-state OH maser survey toward 155 northern star formation regions utilizing the Shanghai Tianma Radio Telescope. In total, we detect 44 6.0 GHz OH masers, 8 of which are new detections (one at 6016 MHz, two at 6030 MHz, and five at 6035 MHz). Of these 44 detected 6.0 GHz OH masers, 13 sites exhibit 6030 MHz OH masers, all 44 sites show the 6035 MHz transition, one site (G009.620+0.194) has the only 6016 MHz OH maser, and one site (W3(OH)) shows the only 6049 MHz OH maser. The 6016 MHz OH maser is the first OH maser of this transition detected in star formation regions. Investigations of the association between 6030/6035 MHz OH masers with 1665 MHz ground-state OH, 6.7 GHz methanol, and 22 GHz water masers show that 1665 MHz OH masers are good indicators of 6.0 GHz OH masers (29% detection rate), which is consistent with previous results. The majority (more than 77%) of 6030 and 6035 MHz OH masers are associated with 6.7 GHz methanol and/or 22 GHz water masers. Comparison between our spectra with previous spectra, we find that only two sources remain fairly stable since their discoveries. We identify 80 Zeeman pairs in 32 6.0 GHz OH maser sites with typical magnetic field strengths of less than 10 mG. The magnetic field directions derived from these 32 maser sites with Zeeman pairs are consistent with previous work, which indicates that the 6.0 GHz OH masers may be potential tracers of the large-scale Galactic magnetic field.